Quantification of the effect of air traffic on terminal precinct ground traffic and the corresponding ground traffic effect on kerbside and parking infrastructure requirements at O.R. Tambo International Airport - Adam, Fatima (Department of Civil Engineering, 2014)
The sharp increase in travel demand at ORTIA in recent years has been translated into frequent parking supply and kerbside pick-up/drop-of bay shortages, particularly during peak periods. This often results in long delays and increased frustration among those using these facilities. In an attempt to solve the terminal precinct congestion problems currently experienced at O.R.Tambo International Airport (ORTIA), a need exists to understand parking and kerbside drop-off/pick-up bay demand, so that infrastructure investment corresponds to this demand.